2021
DOI: 10.1101/2021.06.23.449626
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A critical period of translational control during brain development at codon resolution

Abstract: Translation modulates the timing and amplification of gene expression after transcription. Development of the brain's neocortex requires precisely timed and spatially targeted gene expression, but the relationship between mRNA vs. protein synthesis throughout the genome is unknown. We perform a comprehensive analysis of the reactants, synthesis, and products of mRNA translation spanning mouse neocortex neurogenesis. Ribosome number in the cortical plate decreases sharply at mid-neurogenesis during a transition… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 106 publications
(277 reference statements)
0
11
0
Order By: Relevance
“…Using Ribo-seq, we have generated a valuable new resource for understanding translation at the onset of neurogenesis. To our knowledge, this is one of the first reports to assess wildtype translation using Ribo-seq at the onset of neurogenesis, with exception of a recent pre-print which examined later stages of development ( Harnett et al, 2021 ). scRNAseq studies have revealed that transcripts important for deep and superficial layer neuronal fates are expressed in RGCs Telley et al, 2019 ; however, it’s generally thought that these are translationally repressed until neurons are born.…”
Section: Discussionmentioning
confidence: 99%
“…Using Ribo-seq, we have generated a valuable new resource for understanding translation at the onset of neurogenesis. To our knowledge, this is one of the first reports to assess wildtype translation using Ribo-seq at the onset of neurogenesis, with exception of a recent pre-print which examined later stages of development ( Harnett et al, 2021 ). scRNAseq studies have revealed that transcripts important for deep and superficial layer neuronal fates are expressed in RGCs Telley et al, 2019 ; however, it’s generally thought that these are translationally repressed until neurons are born.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of ribosomal proteins decreases during neuronal differentiation (Harnett et al, 2021; Slomnicki et al, 2016). However, the molecular mechanism of how this coordinated regulation occurs remains elusive.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, most research efforts over the last decades have concentrated on morphogen signaling, epigenetic, and transcriptional mechanisms (Gifford et al, 2013; Loh et al, 2016; Peng et al, 2019; Rogers and Schier, 2011; Stadhouders et al, 2019). However, selective translational control is arguably the primary determinant of regulatory protein abundance in mammals and thus proposed as a central regulator of embryonic cell fate decisions (Harnett et al, 2021; Kong and Lasko, 2012; Kristensen et al, 2013; Lu et al, 2009; Schwanhausser et al, 2011; Teixeira and Lehmann, 2019). Yet, how the developmental transcriptome is selectively translated to authorize cell fate decisions is a fundamental question that remains unclear.…”
Section: Introductionmentioning
confidence: 99%